2007
DOI: 10.1002/dmrr.799
|View full text |Cite
|
Sign up to set email alerts
|

Moderate hypoglycaemia after learning does not affect memory consolidation and brain activation during recognition in non‐diabetic adults

Abstract: One hour of hypoglycaemia at 2.5 mmol/L induced 20-40 min after learning did not disrupt memory consolidation. fMRI did not show evidence of altered brain activation after hypoglycaemia. Consolidation may be relatively resistant to hypoglycaemia, or may have been complete before hypoglycaemia was induced. The study was powered to detect a large effect, and provides some reassurance that moderate hypoglycaemia does not cause major disruption of previously learned memories in people with insulin-treated diabetes. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Consolidation was studied by inducing hypoglycaemia (blood glucose 2.5mmol/l) within 20 to 40 minutes of completing a learning task, 12 and appeared to be unaffected by hypoglycaemia as recall remained intact after euglycaemia had been restored. However, consolidation may have been completed before the hypoglycaemia was induced, and because of the simplicity of the task, it is possible that recognition was being tested rather than memory.…”
Section: Specific Cognitive Functions Affected By Acute Hypoglycaemiamentioning
confidence: 99%
“…Consolidation was studied by inducing hypoglycaemia (blood glucose 2.5mmol/l) within 20 to 40 minutes of completing a learning task, 12 and appeared to be unaffected by hypoglycaemia as recall remained intact after euglycaemia had been restored. However, consolidation may have been completed before the hypoglycaemia was induced, and because of the simplicity of the task, it is possible that recognition was being tested rather than memory.…”
Section: Specific Cognitive Functions Affected By Acute Hypoglycaemiamentioning
confidence: 99%
“…Studies that have examined brain activation in response to sensory stimulation or cognitive challenges using BOLD fMRI during hypoglycemic conditions in nondiabetic subjects (1113) have shown that hypoglycemia reduces regional brain BOLD activation. This reduction in BOLD response during hypoglycemia has been attributed to low glucose levels causing decreases in neuronal activity, glucose oxidative metabolism, cerebral blood flow, neurovascular coupling, and/or neuronal recruitment (12).…”
mentioning
confidence: 99%
“…The association between BGL and BOLD response lies at hand as neuronal activity in the human brain mainly relies on glucose metabolism (Fox and Raichle 2007;Fox et al 1988;Pellerin 1994;Paulson et al 2010). Investigations of effects of BGL on the intensity of the BOLD response during fMRI experiments hitherto mainly focused on BGL significantly lower than those found in 'life-like' situations (Driesen et al 2007;Anderson et al 2006;Warren et al 2008;Schafer et al 2012). These insulin clamp studies give rise to BGL that would usually lead to clinical treatment for hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%